Vingt années de recherches à Oedenburg (Biesheim et Kunheim, Haut-Rhin) : un bilan - Michel Reddé (Gallia)
The Roman archaeological site of Oedenburg (Biesheim et Kunheim, Upper-Rhine) was explored by a French, German and Swiss team from 1998 to 2012 and three successive monographs were published in the Monographien des Römisch-Germanischen Zentralmuseums Mainz. Oedenburg I presents military camps from the Julio-Claudian dynasty; Oedenburg II assesses the research carried out on the religious complex and its surroundings, as well as on the wetlands habitat of the site, with studies of the archaeobotanical and faunal remains; Oedenburg III focuses on the excavation of a sector with a complete stratigraphy of the occupation, from the reign of Tiberius until the Merovingian period. These are accompanied by a comparative study of the pottery from Oedenburg and Augst, as well as a numismatic synthesis. At the same time, several communications from symposiums and different specialist articles were also published. The aim of the present contribution is thus to summarize this abundant French and German bibliography and to propose an overall interpretation of archaeological observations. Lastly, we present questions that remain pending at the end of field operations.Oedenburg is installed on the edge of an arm of the Rhine, which was at that time a braided river flowing over a wide and floodable plain, just opposite the Kaiserstuhl volcano, in Germany. The Celtic oppidum of Breisach is located on the other side of the river, less than 4 km away. The left bank is mainly formed by gravel terraces, with very thin soils, and does not appear to have been conducive to antique agriculture. On the other hand, on the right bank, fertile loess soils abound on the basaltic slopes of Kaiserstuhl.Oedenburg thus appears to have been a practical crossing-point of the river, from where it was easy to reach the region of the Danube sources. From the beginning of the 1st c. AD, we observe the constitution of a crossroads, along a peripheral route bordering the Rhine, from Augst (Switzerland) to Mainz, then Germania inferior and the delta. In addition, the excavations allowed to identify a first early Roman Empire relay, followed by another during late Antiquity.Up until now, no late La Tène levels have been brought to light at the site. The first settlement is a sanctuary enclosure, in 3 AD. Different food waste products were found there, along with monetary offerings, deposits of pottery and Roman weapons, after the arrival of soldiers, during the second decade of our era. The soldiers settled in two successive camps, characteristic of a large troop, but smaller than the size of a legionnaire’s unit. In this way, the garrison filled the void between Argentorate (Strasbourg) and Vindonissa (Windisch, in Switzerland).The first civil agglomeration developed beside the fortification, at a river crossing point. The plan of the agglomeration is primarily known thanks to a vast geomagnetic prospection over a surface of 87 ha. The agglomeration almost totally covers that surface and does not present any regular street organization, nor any monumental public centre, such as those known in the city capitals. Different surveys showed that the installation of public roads was progressive. The recent and widely diffused identification of Oedenburg with the “polis” of Argentovaria, considered as an indigenous capital of Rauraques, beside the Roman colony, thus appears to be very dubious.The wetland zones were conducive to archaeobotanical studies, which showed the importance of Roman military presence through the identification of an association of plants from the Mediterranean or even further away. Faunal studies revealed the role of wild species (birds and fish) in the meat diet, which are rarely brought to light without wet sieving.The departure of the troop, during the conquest of the “Agri decimates”, at the beginning of the reign of Vespasian, did not mark the end of the civil agglomeration. Indeed, the latter continued to develop without interruption until the second half of the 3rd c. Furthermore, we do not observe any levels of destruction after the fall of the limes of Germania superior-Retie, around 260. On the other hand, we observe a progressive abandonment, which became almost total under the Tetrarchy, with a probable movement of the population towards the old oppidum near Breisach, in defence.However, the site of Oedenburg flourished from the year 330 onwards. We observe the construction of a new praetorium road, then of a new fortress, generally attributed to the restorative work of Valentinian I, whose presence at the site is well attested by the Theodosian Code. But was he at Breisach or at Oedenburg itself? The question has not yet been settled, in our opinion, especially as the material brought to light at the latter site cannot be used to establish a secure date. In any case, in the second half of the 4th c., the population agglomerated at the foot of the fortress once again.This situation lasted until the very beginning of the 5th c., after which a largescale abandonment of the site occurred. However, we must bear in mind the fact that the last archaeological levels, just below the topsoil, are very poorly preserved, or even quite often destroyed. The presence of a Merovingian necropolis at the foot of the ramparts, the recent discovery of several plumb engraved with a Chi Rho during prospections, in particular at several hundred meters southwest of the site, in a zone not yet explored by excavations, could argue for a longer human settlement than was initially thought.